Different effects of menopausal hormone therapy on non-alcoholic fatty liver disease based on the route of estrogen administration - Sung Eun Kim; Ji-Song Min; Saemi Lee; Dong-Yun Lee; DooSeok Choi (Scientific Reports, 2023)
Abstract The effects of menopausal hormone therapy (MHT) on non-alcoholic fatty liver disease (NAFLD) were compared based on the route of estrogen administration. The study included 368 postmenopausal women who received MHT for 12 months. Patients were divided into transdermal (n = 75) and oral (n = 293) groups based on the estrogen route. Changes in the prevalence of NAFLD were compared between the two groups before and after 12 months of MHT. In addition, differences in the progression of NAFLD after MHT based on the dose of estrogen and type of progestogen were evaluated in the oral group. After MHT, the prevalence of NAFLD decreased from 24 to 17.3% in the transdermal group but increased from 25.3 to 29.4% in the oral group. Little or no change was found in clinical characteristics and laboratory tests in the transdermal group during MHT. However, serum levels of total cholesterol and low-density lipoprotein cholesterol decreased and triglycerides and high-density lipoprotein cholesterol increased significantly in the oral group. Furthermore, changes in the prevalence of NAFLD were not significantly different based on the dose of estrogen or type of progestogen. Our findings indicate that transdermal estrogen can be beneficial in terms of NAFLD progression.